Chronic Fatigue Persists in a Significant Proportion of Female Patients After Transplantation for Primary Sclerosing Cholangitis. Issue 7 (21st April 2021) - Wunsch, Ewa; Stadnik, Anna; Kruk, Beata; Szczepankiewicz, Benedykt; Kotarska, Katarzyna; Krawczyk, Marcin; Górnicka, Barbara; Wójcicki, Maciej; Milkiewicz, Piotr
Abstract : Chronic fatigue and an impairment of general health‐related quality of life (HRQoL) are frequently reported by patients with primary sclerosing cholangitis (PSC). Studies on patients with primary biliary cholangitis (PBC) suggest that, unlike pruritus, fatigue may not be ameliorated by liver transplantation (LT). However, there are few data regarding the assessment of fatigue before and after transplantation in PSC. To investigate the effect of LT on fatigue and HRQoL in patients with PSC, 81 patients with PSC (median age 33 years; 69% men) were prospectively enrolled in this study. The PBC‐40 and Short Form 36 (SF‐36) questionnaires were used for assessment before and twice after LT. A total of 26 patients who received a transplant for PBC were included as controls. The potential impact of the clinical and laboratory parameters was evaluated by univariate and multivariate analyses. Although in addition to other well‐being indexes the median fatigue score improved after LT ( P  < 0.001), a detailed analysis demonstrated that fatigue persists in one‐third of patients. A significant fatigue reduction was seen in men ( P  < 0.001) but not women ( P  = 0.25). Posttransplant fatigue did not depend on concomitant inflammatory bowel disease, laboratory indexes of cholestasis, or disease recurrence. In the multivariate regression model, female sex was the only independent covariate associated with persistent fatigue. In terms of other measures of HRQoL, LT caused a substantial improvement in the majority of SF‐36 and PBC‐40 domains. Recurrent PSC and unemployment negatively affected the well‐being of patients. Patients who received a transplant for PSC had significantly better HRQoL than those patients with PBC. LT improves various measures of HRQoL, but it does not ameliorate fatigue in female patients with PSC.